2021
DOI: 10.1038/s42003-021-01871-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the dynamic human CEACAM1 monomer-dimer equilibrium

Abstract: Human (h) carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) function depends upon IgV-mediated homodimerization or heterodimerization with host ligands, including hCEACAM5, hTIM-3, PD-1, and a variety of microbial pathogens. However, there is little structural information available on how hCEACAM1 transitions between monomeric and dimeric states which in the latter case is critical for initiating hCEACAM1 activities. We therefore mutated residues within the hCEACAM1 IgV GFCC′ face including V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…[ 73 ] The protein encoded by CEACAM1 have been attributed has been attributed with multiple functions including roles in the differentiation and arrangement of tissue three-dimensional structure, angiogenesis, apoptosis, tumor suppression, and the modulation of innate and adaptive immune responses. [ 74 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 73 ] The protein encoded by CEACAM1 have been attributed has been attributed with multiple functions including roles in the differentiation and arrangement of tissue three-dimensional structure, angiogenesis, apoptosis, tumor suppression, and the modulation of innate and adaptive immune responses. [ 74 ]…”
Section: Discussionmentioning
confidence: 99%
“…These results were unexpected due to the previous association of rare PTVs in the CEACAM gene family with inherited breast cancer risk [ 16 ], the known similarities between breast cancer and CRC risk [ 1 , 17 , 18 ], and the dis-regulation of CEACAM genes in CRC tumors [ 6 , 8 15 ]. Moreover, it has been demonstrated that CEACAM gene function can be affected by even minor genetic changes [ 27 ], and specific residues within CEACAM proteins are crucial for normal function [ 12 , 30 , 31 ].…”
Section: Main Textmentioning
confidence: 99%
“…The Ig V-set domain is crucial for the dimerization of many CEACAM proteins and their ability to function within normal ranges [ 31 , 32 ]. In CEACAM1, mutating particular residues within the Ig V-set domain can affect the monomer-homodimer exchange and result in the protein staying in a monomeric state [ 31 ]. CEACAM1’s ability to dimerize is required for proper function [ 33 36 ].…”
Section: Main Textmentioning
confidence: 99%
“…In addition, IgV-like N-domain containing secreted isoforms also exist 2 . Like other hCEACAM family members, the hCEACAM1 IgV domain serves as the major ligand binding surface and is characterized by the presence of two anti-parallel β-sheets creating two distinct faces, the GFCC′ and ABED faces, respectively 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The major mode of hCEACAM1 binding is homophilic such that it exists on the cell surface as collections of monomers and cis-dimers. This monomer:dimer equilibrium is mainly determined by interactions between the GFCC’ faces of the IgV domains of opposing hCEACAM1 molecules, residues within the transmembrane domain and intracellular calcium concentrations mediated by cellular activation where increased calcium levels promotes hCEACAM1 monomerization 1 , 2 , 7 , 10 . The formation of cell surface hCEACAM1 monomers allows for trans-homophilic or heterophilic interactions critical to the induction of biologic responses 1 , 2 , 7 , 10 .…”
Section: Introductionmentioning
confidence: 99%